Rhetorical Unit “Silk Road” from the Perspectiveof Political Discourse Translation - Gayane Gasparyan; Mari Arzumanyan (Translation Studies: Theory and Practice)
Rhetorical devices, if combined with correctly developed rhetorical strategies, contribute to effective contact with the listeners and prove to be powerful means of immediate impact upon the audience. Figures of speech are among the most significant rhetorical devices, which intensify the expressiveness and emotional impact of a political speech. The term “Silk Road” possessing a long-lasting historical past, has currently acquired metaphorical properties and is often used as a rhetorical device by politicians in different countries and in various circumstance. When public speeches are translated, both the language and socio-cultural context should be carefully examined to maintain the persuasive impact of the original message on the target audience. Hence, a well-done pre-translation discourse analysis of the ST (the text of the uttered speech) will let the translator go deeper into the content-conceptual information and the techniques it is specified by, to identify the verbal and non-verbal elements, which capture the receptor’s attention, leading it simultaneously in the direction intended by the speaker. The article focuses on trilingual (Armenian, English, Russian) analysis of the “Silk Road” rhetorical device in RA Prime Minister’s speech, to specify its function through the socio-cultural situation case study and to identify its translation properties. The narrative, discourse and comparative methods of analyses have been used in the course of research.